Mirtazapine decreased cocaine-induced c-fos expression and dopamine release in rats - Barbosa-Méndez, Susana; Salazar-Juárez, Alberto (Frontiers in Psychiatry, 2024)
Chronic cocaine exposure induces an increase in dopamine release and an increase in the expression of the Fos protein in the rat striatum. It has been suggested that both are necessary for the expression of cocaine-induced alterations in behavior and neural circuitry. Mirtazapine dosing attenuated the cocaine-induced psychomotor and reinforcer effects.Aim -The study evaluates the effect of chronic dosing of mirtazapine on cocaine-induced extracellular dopamine levels and Fos protein expression in rats.Methods -Male Wistar rats received cocaine (10 mg/Kg; i.p.) during the induction and expression of locomotor sensitization. The mirtazapine (30 mg/Kg; MIR), was administered 30 minutes before cocaine during the cocaine withdrawal. After each treatment, the locomotor activity was recorded for 30 minutes. Animals were sacrificed after treatment administration. Dopamine levels were determined by high-performance liquid chromatographic (HPLC) in the ventral striatum, the prefrontal cortex (PFC), and the ventral tegmental area (VTA) in animals treated with mirtazapine and cocaine. The quantification of c-fos immunoreactive cells was carried out by stereology analysis.-Mirtazapine generated a decrease in cocaine-induced locomotor activity. In addition, mirtazapine decreased the amount of cocaine-induced dopamine and the number of cells immunoreactive to the Fos protein in the striatum, PFC, and VTA.Conclusion -These data suggest that mirtazapine could prevent the consolidation of changes in behavior and the cocaine-induced reorganization of neuronal circuits. It would explain the mirtazapine-induced effects on cocaine behavioral sensitization. Thus, these data together could support its possible use for the treatment of patients with cocaine use disorder.